Implementation of dynamic biological process models into a reference net simulation environment - Pettigrew, Liam; Hubert, Stefan; Groß, Frauke; Delgado, Antonio (Simulation in Production and Logistics, 2015)
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.implem

Messtechnische Datenerfassung und -analyse zur Prozessregelung einer dezentralen Abwasseraufbereitungsanlage - Fröba, Laura; Pettigrew, Liam; Vega De Lille, Marisela Ix Chel; Groß, Frauke; Delgado, Antonio (Proceedings der 22. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2014)
UnivIS-Import:2015-04-17:Pub.2014.tech.ITC.stmmec.messte

Modified ADM1 for high-rate anaerobic co-digestion of thermally pre-treated brewery surplus yeast wastewater - Pettigrew, Liam; Gutbrod, Alexander; Domes, Herbert; Groß, Frauke; Méndez-Contreras, Juan M.; Delgado, Antonio (Water Science and Technology, 2017)
Co-digestion of surplus yeast with brewery wastewater is a potentially economical method for recovering energy, in the form of biogas, from this difficult to dispose of by-product. In this work a modified version of the ADM1 (Anaerobic Digestion Model No. 1) was calibrated for an anaerobic digester fed with thermally pre-treated brewery yeast surplus wastewater. The model could predict changes to reactor methane production and reduction of biodegradable matter when fed with both pre-treated and untreated yeast surplus wastewater at varying loading rates. Model calibration focused on low temperature thermal pre-treatment as experiments into a combined thermal-alkaline pre-treatment did not show any significant improvements. A low temperature pre-treatment of 60 °C for 30 minutes was sufficient for yeast inactivation and allowed for stable and more efficient operation of the high-rate anaerobic digester over a period of 232 days. The low temperature and time for pre-treatment also reduced the evaporation of easily biodegradable residual ethanol present in the influent, while still maintaining a low level of suspended matter. Inline measurements of gas composition, production and effluent chemical oxygen demand were sufficient for reliable model calibration of these same outputs. More detailed characterization of influent and effluent is required if organic acid concentrations for pH control are needed.
UnivIS-Import:2018-02-22:Pub.2017.tech.ITC.stmmec.modifi
Keywords: ADM1; Brewery wastewater; Co-digestion; Pre-treatment; Surplus yeast

Optimisation of water usage in a brewery clean-in-place system using reference nets - Pettigrew, Liam; Blomenhofer, Verena; Hubert, Stefan; Groß, Frauke; Delgado, Antonio (Journal of Cleaner Production, 2015)
The brewery industry is becoming increasingly aware of its water and energy usage due to stricter regulations, and environmental and economic incentives. An area where large improvements in water usage presents itself is the clean-in-place system. A significant portion of the total process water required in an industrial sized brewery is used during clean-in-place processes. Testing and optimisation of these industrial processes can be quickly and economically achieved using computer modelling and simulation tools. One such tool is the reference net, a subclass of object-oriented Petri nets. In order to predict the water usage and the potential for energy production from wastewater attributed to the clean-in-place plant in a brewery, the reference net formalism is used. Validation of the complete reference net system is undertaken using two sets of simulations, one set of simulations running an approximation of a standard brewery clean-in-place system and a second set implementing a fuzzy logic adaptive control for water reuse. The reference net is found to be a valid and efficient tool for quick prototyping of new and existing industrial sized brewery clean-in-place systems.
UnivIS-Import:2015-03-09:Pub.2015.tech.ITC.stmmec.optimi
Keywords: Brewery; Clean-in-place; Fuzzy logic; Petri nets; Reference nets; Water usage

Simulation-based optimisation of wastewater flow and composition for on-site treatment in the food and beverage industry utilising reference nets in combination with genetic algorithms - Hubert, Stefan; Pettigrew, Liam; Helmers, Thorben; Mießner, Ulrich; Groß, Frauke; Räbiger, Norbert; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2015-07-08:Pub.2014.tech.ITC.stmmec.simula_4